Inosine Triphosphate Pyrophosphatase and NUDT15 are Good Predictors of Clinical Outcomes in Thiopurine-Treated Chinese Patients with Inflammatory Bowel Disease. Issue 3 (June 2022) - Luo, Xuemei; Yan, Simin; Jin, Lu; Zhu, Huaijun; Zhang, Xiaoqi; Ge, Weihong
Abstract : Background: Although the relationship between NUDT15 and thiopurine-induced leukopenia has been proven in previous studies, no prominent factors explaining interindividual variations in its active metabolite, 6-thioguanine nucleotide (6-TGN), and clinical efficacy have been identified. In this study, the correlation between genotypes (thiopurine S-methyltransferase, NUDT15, and ITPA polymorphisms), 6-TGN concentrations, and clinical outcomes (efficacy and side effects) in patients with inflammatory bowel disease were investigated. Methods: In total, 160 patients with inflammatory bowel disease were included, and the 3 genotyped genes and 6-TGN levels were measured by high-performance liquid chromatography. Statistical analyses and calculations were performed to determine their relationships. Results: ITPA genotypes and 6-TGN concentration were both associated with the clinical effectiveness of azathioprine ( P = 0.036 and P = 4.6 × 10 −7 ), with a significant correlation also detected between them ( P = 0.042). Patients with ITPA variant alleles exhibited higher 6-TGN levels than those with the wild-type allele. In addition, the relationship between NUDT15 and leukopenia and neutropenia was confirmed ( P = 1.79 × 10 −7 and 0.002). Conclusions: In summary, it is recommended that both ITPA and NUDT15 genotyping should be performed before azathioprine initiation. Moreover, the 6-TGN concentration should be routinely monitored during the later period of treatment.